2017
DOI: 10.1088/1674-4527/17/7/70
|View full text |Cite
|
Sign up to set email alerts
|

Surface thermophysical properties on the potentially hazardous asteroid (99942) Apophis

Abstract: In this work, we investigate the surface thermophysical properties (thermal emissivity, thermal inertia, roughness fraction and geometric albedo) of asteroid (99942) Apophis, using the currently available thermal infrared observations of CanariCam on Gran Telescopio CANARIAS and far-infrared data by PACS of Herschel, on the basis of the Advanced thermophysical model. We show that the thermal emissivity of Apophis should be wavelength dependent from 8.70 µm to 160 µm, and the maximum emissivity may arise around… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Our derived thermal inertia result overlaps with estimated ranges cited in the previous studies. The same study by Müller et al (2014b) found a thermal inertia in the range of 250-800 J m −2s 1 2 K −1 with a best fit at 600 J m −2 - forward by Yu et al (2017). For comparison, Itokawa-an asteroid very similar to Apophis in size and taxonomic classwas measured to have Γ = 700 ± 200 J m −2s 1 2 K −1 by Müller et al (2014a).…”
Section: Thermal Models and Resultsmentioning
confidence: 84%
“…Our derived thermal inertia result overlaps with estimated ranges cited in the previous studies. The same study by Müller et al (2014b) found a thermal inertia in the range of 250-800 J m −2s 1 2 K −1 with a best fit at 600 J m −2 - forward by Yu et al (2017). For comparison, Itokawa-an asteroid very similar to Apophis in size and taxonomic classwas measured to have Γ = 700 ± 200 J m −2s 1 2 K −1 by Müller et al (2014a).…”
Section: Thermal Models and Resultsmentioning
confidence: 84%
“…( 83 J m −2 K −1 s −1/2 matches very well. (99942) Apophis: For this object, we found four TI estimates (Müller et al 2014b;Licandro et al 2016;Yu et al 2017;Satpathy et al 2022), which are not always consistent or are subject to large uncertainties. Nevertheless, we include it in our validation list.…”
Section: Model Testing-further Verification On the Near-earth Asteroidsmentioning
confidence: 89%
“…Additionally, while an impact in 2029 has been ruled out, the potential for a future collision cannot be disregarded, and further study of the object is needed to refine this. In particular, the Yarkovsky effect has been shown to significantly alter predictions beyond 2029 and is sensitive to the physical parameters of Apophis, such as its albedo, diameter, and density (Farnocchia et al 2013;Yu et al 2017).…”
Section: Availability Of Solar System Bodiesmentioning
confidence: 99%